First‐line treatment selection and early monitoring patterns in chronic phase‐chronic myeloid leukemia in routine clinical practice: SIMPLICITY. Issue 11 (25th September 2017) - Goldberg, Stuart L.; Cortes, Jorge E.; Gambacorti‐Passerini, Carlo; Hehlmann, Rüdiger; Khoury, H. Jean; Michallet, Mauricette; Paquette, Ron L.; Simonsson, Bengt; Zyczynski, Teresa; Foreman, Aimee; Abruzzese, Elisabetta; Andorsky, David; et al.
Abstract: Achieving successful outcomes in chronic phase‐chronic myeloid leukemia (CP‐CML) requires careful monitoring of cytogenetic/molecular responses (CyR/MR). SIMPLICITY (NCT01244750) is an observational study exploring tyrosine kinase inhibitor use and management patterns in patients with CP‐CML receiving first‐line imatinib ( n = 416), dasatinib ( n = 418) or nilotinib ( n = 408) in the US and 6 European countries in routine clinical practice. Twelve‐month follow‐up data of 1242 prospective patients (enrolled October 01 2010‐September 02 2015) are reported. 81% of patients had baseline comorbidities. Treatment selection was based on perceived efficacy over patient comorbidity profile. There was a predominance of imatinib‐treated patients enrolled earlier in the study, with subsequent shift toward dasatinib‐ and nilotinib‐treated patients by 2013/2014. Monitoring for either CyR/MR improved over time and was documented for 36%, 82%, and 95% of patients by 3, 6, and 12 months, respectively; 5% had no documentation of CyR/MR monitoring during the first year of therapy. Documentation of MR/CyR testing was higher in Europe than the US ( P < .001) and at academic versus community practices ( P = .001). Age <65 years, patients being followed at sites within Europe, those followed at academic centers and patients no longer on first‐line therapy were more likely to be monitored by 12 months. SIMPLICITY demonstrates that the NCCN and ELN recommendations on response monitoring have not been consistently translated into routine clinical practice. In the absence of appropriate monitoring practices, clinical response to TKI therapy cannot be established, any needed changes to treatment strategy will thus not be implemented, and long‐term patient outcomes are likely to be impacted.